A REVIEW OF THE USE OF RANKINE CYCLE SYSTEMS FOR HYDROGEN PRODUCTION - Novosel, Urška; Avsec, Jurij (Journal of Energy Technology, 2024)
The vast majority of steam power plants in the world are based on the Rankine cycle. It is a well-known, trustworthy process that uses water or water vapour as a working medium, which supplies heat from various primary energy sources: fossil fuels, renewable energy sources (solar energy, energy from wood biomass, etc.) or a combination of both. With the Rankine cycle, energy sources other than electricity can be produced, which can be used as the primary energy source for various applications. The present article focuses on the production of hydrogen in addition to electricity; therefore, two energy sources are obtained from the same system with a few modifications of the existing power plant for further exploitation. There are several processes for hydrogen production using the Rankine cycle; in the present article, two processes are focused on: using part of the elec- tricity produced and obtaining hydrogen by electrolysis of water or using part of high quality steam (basically heat energy) in combination with electricity and obtaining hydrogen by a thermochemi- cal copper-chlorine process. Each of these processes has its advantages and disadvantages, which are presented in the present article with an example model of a power plant.